ANALISA PENGEMBANGAN JARINGAN IRIGASI AIR TANAH (JIAT) KABUPATEN GUNUNG KIDUL - Suharyanto, Indra; Arifin, Muhamad; Saka, Aji (Fakultas Teknik Universitas Cokroaminoto Yogyakarta, 2023)
The development of the Groundwater Irrigation Network (JIAT) invites all residents at several points in the Gunungkidul Regency to support agricultural activities by utilizing water from below the ground surface using water pumps so that they can distribute water needs for irrigation purposes. This study aims to determine the amount of irrigation water needs with several variations of cropping patterns. So that the development of the Groundwater Irrigation Network (JIAT) can increase agricultural productivity in Gunungkidul Regency. From the results of research through a survey at each location of the Groundwater Irrigation Network (JIAT) in Gunungkidul Regency, it shows that in order to increase agricultural productivity, special maintenance or rehabilitation costs are needed in order to get periodic maintenance that is heavy repair or replacement of components in the irrigation network, as a form of food security national.